Waiting Patiently: An Empirical Study of Queue Abandonment in an Emergency Department - Batt, Robert J.; Terwiesch, Christian (Management Science, 2015)
We study queue abandonment from a hospital emergency department. We show that abandonment is influenced by the queue length and the observable queue flows during the waiting exposure, even after controlling for wait time. For example, observing an additional person in the queue or an additional arrival to the queue leads to an increase in abandonment probability equivalent to a 25-minute or 5-minute increase in wait time, respectively. We also show that patients are sensitive to being “jumped” in the line and that patients respond differently to people more sick and less sick moving through the system. This customer response to visual queue elements is not currently accounted for in most queuing models. Additionally, to the extent the visual queue information is misleading or does not lead to the desired behavior, managers have an opportunity to intervene by altering what information is available to waiting customers. This paper was accepted by Yossi Aviv, operations management.